Towards enhanced durability of electrochromic WO3 interfaced with liquid or ceramic sodium-based electrolytes. (10th November 2020) - Zimmer, Alexandre; Tresse, Manuel; Stein, Nicolas; Horwat, David; Boulanger, Clotilde
Abstract: The reversible intercalation of sodium ion into tungsten oxide WO3 appears as an interesting alternative to hydrogen or lithium ion reduction in order to get the characteristic transition from clear transparent to bluish coloration in electrochromic devices, but it has been comparatively less considered. In order to address further viable all-ceramic devices based on sodium ion intercalation and overcome the issue of WO3 degradation in aqueous media, three configurations of WO3 thin film-based electrochromic half-cells were tested, namely in (i) aqueous acidified Na2 SO4 electrolyte, (ii) room temperature ionic liquid BEPipTFSI electrolyte and (iii) aqueous acidified Na2 SO4 electrolyte associated with an amorphous NASICON-cap onto WO3 film. We compared their electro-optical characteristics during 100 voltammetry cycles, including the Na + diffusion coefficient calculated through electrochemical method. It is found that sputter-deposited amorphous WO3 thin films on transparent conductive substrates is promising for electrochromic all-ceramic devices based on Na ion insertion. Electrochemical characterization in aqueous medium is not relevant to extract relevant data when WO3 is in direct contact with the electrolyte as the electrochromic film is progressively dissolved. In contrast, WO3 capped with oxide amorphous Na-ion conductor readily operates over 100 cycles, the capping layer preventing degradation by the aqueous medium. Alternatively, ionic liquid does not degrade the WO3 film and can be employed to efficiently characterize the electro-optical performances. Graphical abstract: Image, graphical abstract